2018
DOI: 10.17556/erziefd.346487
|View full text |Cite
|
Sign up to set email alerts
|

Fen Bilimleri Öğretmen Adaylarının Çevre Bilimi Dersi Kapsamında Gerçekleştirilen Alan Gezisi Deneyimleri

Abstract: The purpose of this study is to determine the thoughts and experiences of pre-service science teachers regarding scientific field trip. In the study, mixed methods including quantitative and qualitative dimensions were used. For quantitative data questionnaire technique and for qualitative data phenomenological designs were used. The sample of the study was composed of 41 pre-service science teachers who were all juniors. The data was collected using an questionnaire form which developed by researchers. Conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Alanyazında, okul dışı öğrenmenin bir dizi faydasını belirten birçok çalışma bulunmaktadır. Örneğin, Doğan, Çiçek & Saraç (2018) araştırması, okul dışı öğrenmenin derse öğrenilen teorik bilgileri uygulamalı olarak tamamlama, çevreyi tanıma, ortak hareket etme ve iş bölümü yapma, gözlem yapma, inceleyerek yeni bilgiler kazanma, bilgilerin kalıcı olması, dersi günlük yaşamla ilişkilendirme, konu ile ilgili gözlem yapma ve teorik bilgileri pratiğe aktarma gibi faydalarını ortaya koymuştur. Vivier & Lee (2018) ise, okul dışı öğrenmenin hem akademik hem de akademik olmayan faydalarının olduğunu ifade etmiştir.…”
Section: öğRencilerin Gerçekleştirilen Etkinlikler Hakkında öNerileriunclassified
“…Alanyazında, okul dışı öğrenmenin bir dizi faydasını belirten birçok çalışma bulunmaktadır. Örneğin, Doğan, Çiçek & Saraç (2018) araştırması, okul dışı öğrenmenin derse öğrenilen teorik bilgileri uygulamalı olarak tamamlama, çevreyi tanıma, ortak hareket etme ve iş bölümü yapma, gözlem yapma, inceleyerek yeni bilgiler kazanma, bilgilerin kalıcı olması, dersi günlük yaşamla ilişkilendirme, konu ile ilgili gözlem yapma ve teorik bilgileri pratiğe aktarma gibi faydalarını ortaya koymuştur. Vivier & Lee (2018) ise, okul dışı öğrenmenin hem akademik hem de akademik olmayan faydalarının olduğunu ifade etmiştir.…”
Section: öğRencilerin Gerçekleştirilen Etkinlikler Hakkında öNerileriunclassified
“…Considering studies in the related literature, studies that examine the effects of out-of-class teaching activities on cognitive objectives with experimental methods outnumbered (Şahin & Sağlamer Yazgan, 2013;Bozdoğan & Kavcı, 2016;Bodur & Yıldırım, 2018;Borsos, Borić, & Patocskai, 2018;Durel, 2018;Sontay & Karamustafaoğlu, 2018;Avcı & Gümüş, 2020). However, some studies reported that out-of-class activities positively affect objectives in the affective field, which is indeed difficult to observe (Doğan, Çiçek, & Saraç, 2017;Yavuz Topaloğlu & Balkan Kıyıcı, 2018;Yıldırım, 2018). Out-of-class learning processes, which are an important part of contemporary education, can include activities lasting from a few minutes to days (Donaldson & Goering, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…There are many research on field trips area (Achen, Warren, Fazzari, Jorich, & Thorne, 2019;Bozdogan, 2012Bozdogan, , 2016Cetin, 2014;Dogan, Cicek;& Sarac, 2018;Kamen & Leri, 2019;Turkmen, Topkac, & Atasayar Yamik, 2016). In the study of Turkmen et al (2016), five grade students found the Natural History Museum in Izmir as fun despite the fact that they were not very pleased with Botanical Garden in Izmir.…”
Section: Introductionmentioning
confidence: 99%